The Emergence and Evolution of Consumer Language Research - Packard, Grant; Berger, Jonah (Journal of Consumer Research, 2024)
Abstract Over the last 50+ years, there has been a huge rise in interest in consumer language research. This article spotlights the emergence and evolution of this area, identifying key themes and trends and highlighting topics for future research. Work has evolved from exploration of broad language concepts (e.g., rhetorics) to specific linguistic features (e.g., phonemes) and from monologues (e.g., advertiser to consumer) to two-way dialogues (e.g., consumer to service representative and back). We discuss future opportunities that arise from past trends and suggest two important shifts that prompt questions for future research: the new shift toward using voice (vs. hands) when interacting with objects and the ongoing shift toward using hands (vs. voices) to communicate with people. By synthesizing the past, and delineating a research agenda for the future, we hope to encourage more researchers to begin to explore this burgeoning area.